2021
DOI: 10.35848/1882-0786/ac1230
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of high wall-plug efficiency III-nitride micro-light-emitting diodes with MOCVD-grown tunnel junction contacts using chemical treatments

Abstract: High wall-plug efficiency (WPE) micro-light-emitting diodes with metalorganic chemical vapor deposition-grown tunnel junction (TJ) contacts are demonstrated. By employing chemical treatments before sidewall activation, the 20 × 20 μm 2 TJ devices resulted in a voltage penalty of 0.2 V at 20 A cm −2 , compared to devices with indium-tin oxide (ITO) contacts. Moreover, the enhancement in light output power was more than 40% higher than ITO devices. Hence, the TJ devices yielded the peak external quantum efficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…It should be noted that these numbers depend heavily on both the AlInGaP pixel efficiency as well as the InGaN pixel efficiency. Up to 1.5x higher InGaN efficiencies in this range of pixel sizes have been reported by groups at UCSB (Hwang 2017, Wong 2021). If such efficiencies can be sustained in mass manufacturing of blue microLEDs, the crossover point for higher efficiency from downconversion would increase to approximately 10 m.…”
Section: Resultsmentioning
confidence: 56%
“…It should be noted that these numbers depend heavily on both the AlInGaP pixel efficiency as well as the InGaN pixel efficiency. Up to 1.5x higher InGaN efficiencies in this range of pixel sizes have been reported by groups at UCSB (Hwang 2017, Wong 2021). If such efficiencies can be sustained in mass manufacturing of blue microLEDs, the crossover point for higher efficiency from downconversion would increase to approximately 10 m.…”
Section: Resultsmentioning
confidence: 56%
“…To distinguish the effect of passivation on the performance of Micro-LED devices, three different types of devices were fabricated: S1 is used for Micro-LEDs without passivation, S2 is labeled for Micro-LEDs with PECVD sidewall passivation, and S3 is used to designate the Micro-LEDs with sol-gel sidewall passivation. Using analysis methods such as electroluminescence (EL), current-voltage (I-V), external quantum efficiency (EQE), and wall plug efficiency (WPE) [ 10 , 26 ], we compared the device characteristics of Micro-LEDs with different sizes and passivation types, including without passivation, sol-gel SiO 2 , and PECVD SiO 2 . Our results showed that sol-gel passivation has considerable optimization potential for Micro-LEDs.…”
Section: Resultsmentioning
confidence: 99%
“…The slope efficiency was quite low, and we attribute this to strong scattering loss at the facets due to the imperfect RIE etching. We believe further improvements in the growth conditions, as well as the optimization of experimental structure, doping, inclusion of tunnel junctions [33], chemical treatments [34], vertical mirror facet formation [35] and bonding will lead to better L-I-V characteristics. In the past, researchers reported nearly vertical facet formation in the semipolar LDs by Cl 2 gas/Ar-ion chemically assisted ion beam etching (CAIBE) in an Oxford Ion Mill system [35]; as a result, our future investigations will include this method for on-wafer facet formation.…”
Section: On-wafer Rie Facet Formationmentioning
confidence: 99%